Synthesis of Carbapyochelins via Diastereoselective Azidation of 5-(Ethoxycarbonyl)methylproline Derivatives - Liyanage, Wathsala (2008)
Two configurationally stable carbon-based analogues of pyochelin have been prepared from Boc-pyroglutamic acid-tert-butyl ester in 11 and 13 steps. Introduction of the amino group was achieved by a highly diastereoselective electrophilic azidation reaction to afford novel bis-α-amino acid proline derivatives. [Image: see text]